Risc management: the medical support system in contemporary armed conflict - CIRLAN, Sergiu; MARFIN, Andrei; DUMITRAS, Vasile (One Health & Risk Management, 2023)
Introduction. Contemporary armed conflicts are characterized by a multifaceted blend of combat strategies, encompassing conventional and unconventional weaponry, regular and irregular forces, terrorist actions and acts of organized crime, indiscriminate violence and outside international law.Material and methods. A retrospective bibliographic study was conducted on the evolution of combat strategies employed by the U.S. Armed Forces, NATO member countries, and international UN Peacekeeping Operations over the past 25 years.Results. The way of organizing and providing medical assistance in local military conflict differs from the principles governing medical support in major armed conflicts. The staging of the treatment system and the evacuation of the wounded follows a crucial time-based framework known as the '10-1-2(+2)' rule: "10"– immediate measures to stop bleeding within 10 minutes of the injury; "1" – evacuation to the medical treatment facility capable of performing resuscitation and stabilizing vital functions.; "2" – timely transfer to a medical formation equipped for Damage Control Surgery and Resuscitation within 2 hours of the injury; "+2" – performing the surgical intervention, stabilization of vital functions, and diagnostic preparations for strategic evacuation within 4 hours of the injury.Conclusions. Resulting from the specific particularities of the local military conflict, the planning of medical support as well as the complex of treatment and evacuation measures, force health protection, medical logistics, require adaptation to the real tactical and medical situation created.